Impact of a Complement Factor H Gene Variant on Renal Dysfunction, Cardiovascular Events, and Response to ACE Inhibitor Therapy in Type 2 Diabetes - Valoti, Elisabetta; Noris, Marina; Perna, Annalisa; Rurali, Erica; Gherardi, Giulia; Breno, Matteo; Parvanova Ilieva, Aneliya; Petrov Iliev, Ilian; Bossi, Antonio; Trevisan, Roberto; Dodesini, Alessandro Roberto; Ferrari, Silvia; et al. (Frontiers in Genetics, 2019)
Complement activation has been increasingly implicated in the pathogenesis of type 2 diabetes and its chronic complications. It is unknown whether complement factor H (CFH) genetic variants, which have been previously associated with complement-mediated organ damage likely due to inefficient complement modulation, influence the risk of renal and cardiovascular events and response to therapy with angiotensin converting enzyme inhibitors (ACEi) in type 2 diabetic patients. Here we have analyzed the c.2808G>T, (p.Glu936Asp) CFH polymorphism, which tags the H3 CFH haplotype associated to low plasma factor H levels and predisposing to atypical hemolytic uremic syndrome, in 1158 type 2 diabetics prospectively followed in the BENEDICT trial that evaluated the effect of the ACEi trandolapril on new onset microalbuminuria. At multivariable Cox analysis the p.Glu936Asp polymorphism (Asp/Asp homozygotes, recessive model) was associated with increased risk of microalbuminuria (adjusted HR 3.25 [95% CI, 1.46-7.24], P=0.0038) and cardiovascular events (adjusted HR 2.68 [95% CI 1.23-5.87], P=0.013). The p.Glu936Asp genotype significantly interacted with ACEi therapy in predicting microalbuminuria. ACEi therapy was not nephroprotective in Asp/Asp homozygotes (adjusted HR 1.54 [0.18-13.07], P=0.691 vs. non-ACEi treated Asp/Asp patients), whereas it significantly reduced microalbuminuria events in Glu/Asp or Glu/Glu patients (adjusted HR 0.38 [0.24-0.60], P<0.0001 vs. non-ACEi treated Glu/Asp or Glu/Glu patients). Among ACEi treated patients, the risk of developing cardiovascular events was higher in Asp/Asp homozygotes than in Glu/Asp or Glu/Glu patients (adjusted HR 3.26 [1.29-8.28], P=0.013). Our results indicate that type 2 diabetic patients Asp/Asp homozygotes in the p.Glu936Asp CFH polymorphism are at increased risk of microalbuminuria and cardiovascular complications and may be less likely to benefit from ACEi therapy. Further studies are required to confirm our findings.